Odpowiedzi

2010-03-07T18:58:43+01:00
28*(17-15)= 28*2=56
135*(134-133)=135*1=135
31*(15-2*7)=31*(15-14)=31*1=31
6*(2*13-26)=6*(23-26)=6*0=0
13*(49-2*27)=13*(49-54)=13*(-5)=-65
57*(57-55)=57*2=114
1 1 1
2010-03-07T20:07:09+01:00
6. Oblicz sprytnie ( wyłącz wspólny czynnik przed nawias ).
a) 28* 17- 28* 15=28(17-15)= 28*2=56
b) 134* 135- 133* 135=135(134-133)=135*1=135
c) 31* 15- 62* 7=31(15-2*7)=31(15-14)=31*1=31
d) 12* 13- 6* 26=6(2*13-26)=6(26-26)=6*0=0
e) 13* 49- 26* 27=13(49-2*27)=13(49-54)=13*(-5)=-65
f) 57²- 57* 55=57(57-55)=57*2=114
1 5 1
Najlepsza Odpowiedź!
2010-03-08T00:42:20+01:00
6. Oblicz sprytnie ( wyłącz wspólny czynnik przed nawias ).
a) 28* 17- 28* 15= 28*(17-15) = 28*2 = 56
b) 134* 135- 133* 135= 135*( 134 - 133) = 135 * 1 = 135
c) 31* 15- 62* 7= 31*(15 - 2*7) = 31*(15-14)=31*1 = 31
d) 12* 13- 6* 26=13*(12-6*2) = 13*(12-12) = 13*0=0
e) 13* 49- 26* 27= 13*(49 - 2*27) = 13 * (49 - 54) = 13*(-5) = -65
f) 57(do drugiej potęgi)- 57* 55 =
57² - 57 * 55 = 57*(57 - 55) = 57*2 = 114

POZDRAWIAM :)